2019
DOI: 10.1051/bmdcn/2019090320
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of nigellasativaoil on the prevention of phlebitis induced by chemotherapy: a clinical trial

Abstract: Introduction: Phlebitis, that disrupts chemotherapy, is the inflammation of the vein and the most common complication of intravenous injection of chemotherapy drugs. Aim: the aim was determine the effect of topical application of N. sativa oil on the prevention of phlebitis caused by chemotherapy. Methods: This single-blind clinical trial was conducted on 60 cancer patients. In the intervention group, five drops of N. sativa oil was applied on the distal area of the catheter, two times per day and every 12 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We selected four human studies (Table 2) that described the effect of N. sativa on human cancer [12][13][14][15]. In three days, Behnamfar et al analyzed the incidence and magnitude of phlebitis, applying N. Sativa by a catheter upon the peripheral vein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected four human studies (Table 2) that described the effect of N. sativa on human cancer [12][13][14][15]. In three days, Behnamfar et al analyzed the incidence and magnitude of phlebitis, applying N. Sativa by a catheter upon the peripheral vein.…”
Section: Resultsmentioning
confidence: 99%
“…In three days, Behnamfar et al analyzed the incidence and magnitude of phlebitis, applying N. Sativa by a catheter upon the peripheral vein. In their research, they reported that the prevalence of phlebitis in the control group was optimum and that the occurrence of phlebitis in the intervention group was lowest during the 72 hours of the test, assuming that N. sativa oil seemed to have a massive effect on the intervention group [12]. Hussain et al demonstrated the effect of applying N. sativa oil on acute myeloid leukemia.…”
Section: Resultsmentioning
confidence: 99%
“…Phlebitis is an inflammation of the vein caused by chemical, mechanical, or infectious irritation (Gorski, 2017; Higginson & Parry, 2011). Several pharmacological interventions (e.g., nonsteroidal antiinflammatory drugs (NSAIDs) (Berardi et al, 2003), heparin (Ikeda, Douchi, & Nagata, 2004), steroid ointment (Hamabe et al, 2017), and traditional medicines such as Sesame indicum (Bigdeli Shamloo et al, 2019), Nigella sativa (Behnamfar, Parsa Yekta, Mojab, & Kazem Naeini, 2019), and potato (Zhang, Jin, & Wang, 2018)) have been suggested to help reduce incidence of infusion phlebitis and CIP. However, the number of evidences is limited and it is yet unknown what are the most efficient methods.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore when using intravenous infusion catheters for chemotherapy, nurse must take care of infusion principles such as skin antisepsis, safe maintenance of solutions, and prevention of complications such as air embolism, infection, catheter damage (Behnamfar et al, 2019). The incidence of chemotherapy induced phlebitis in cancer patients ranged from 35% to 56%.…”
Section: Introductionmentioning
confidence: 99%